The Role Of Islamic Spirituality In Improving Psychological Well-Being Among The Elderly Palangka Raya City - Sahduari, Sahduari; Surawan, Surawan (Yayasan Nanggroe Aceh Mulia, 2025)
This study discusses how Islamic spirituality contributes to improving the mental well-being of elderly people in Palangka Raya. Elderly people often experience declines in physical, mental, and social health, which can lead to depression, anxiety, and feelings of loneliness due to loss, health problems, and social isolation. Although awareness of mental health is growing, services aimed at the elderly in Palangka Raya are still very minimal. Using qualitative methods and conducting interviews with two elderly Muslims aged over 60 years, this study found that spirituality in the context of Islam provides inner peace through worship practices such as prayer, increases gratitude, strengthens social relationships, and provides meaning in life. In particular, prayer brings peace and helps the elderly to remain grateful, even in the midst of challenges. Spiritual activities also promote social support and close interpersonal relationships. Elderly people who have strong spirituality usually have a deep belief in life after death, which gives them purpose and meaning in life, and helps them cope with the difficulties that arise in old age. It is hoped that this study can be an important source of information for the community and contribute to the development of theories and practices of spirituality in elderly care.